Hubungan Ketidaknyamanan Dalam Kehamilan Terhadap Kualitas Tidur Ibu Hamil Trimester III di TPMB D Jakarta - Susilawati, Dewi; Damayanti, Dewi Suri; Jumhati, Siti; Pustikasari, Atikah (Jurnal Ilmiah Kesehatan, 2024)
Abstract As pregnancy progresses, pregnant women tend to experience sleep problems. These sleep disturbances are generally caused by physical changes during pregnancy that trigger discomfort. In addition, pregnant women who have certain diseases are also at risk of sleep disorders. Poor sleep can cause complications in pregnancy. Research Objective: To determine the relationship between discomfort and sleep quality in third trimester pregnant women at TPMB ‘D’ Tebet South Jakarta. Research Methods: Descriptive quantitative with cross-sectional design. Sample 40 respondents with total sampling technique. The research instrument used a discomfort questionnaire and PSQI. Data analysis using Chi-square test. Research results: Most of the respondents experienced discomfort in the category of disturbance as many as 25 respondents (62.5%). Most of the respondents had poor sleep quality as many as 23 respondents (57.5%). Based on the Chi-square test, the p-value <0.000 is smaller than 0.05, it is concluded that there is a relationship between discomfort and sleep quality in third trimester pregnant women at TPMB D Tebet South Jakarta, thus Ha is accepted. Keywords : Pregnant women, discomfort, sleep quality